2004
DOI: 10.1002/ana.20008
|View full text |Cite
|
Sign up to set email alerts
|

Blood transcriptional signatures of multiple sclerosis: Unique gene expression of disease activity

Abstract: Multiple sclerosis (MS) is a central nervous system disease with an unpredictable course and outcome. Peripheral blood mononuclear cells (PBMCs) are involved in the disease pathogenesis and induce active demyelination. Using oligonucleotide microarrays, we identified a statistically significant transcriptional signature of 1,109 genes in PBMCs from 26 MS patients, irrespective of disease activation state or immunomodulatory treatment. This signature contains genes that implicate underlying processes involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
93
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 49 publications
11
93
0
1
Order By: Relevance
“…19,[20][21][22] Additionally, recent microarray studies in human CNS disorders (multiple sclerosis, stroke and seizure) as well as rodent models of such disease suggest specific gene expression signatures in PBMCs. 23,24 Microarrays allow high-throughput gene expression profiling of transcriptional reactivity. Applied to PBMCs, they may detect signatures of biological processes that underlie adaptive and pathological reactions to traumatic stress as they unfold over time.…”
mentioning
confidence: 99%
“…19,[20][21][22] Additionally, recent microarray studies in human CNS disorders (multiple sclerosis, stroke and seizure) as well as rodent models of such disease suggest specific gene expression signatures in PBMCs. 23,24 Microarrays allow high-throughput gene expression profiling of transcriptional reactivity. Applied to PBMCs, they may detect signatures of biological processes that underlie adaptive and pathological reactions to traumatic stress as they unfold over time.…”
mentioning
confidence: 99%
“…These previous studies demonstrated changes in PB gene expression patterns with among these, genes involved in the p53 and apoptosis pathway. [17][18][19][20][21] Whereas these studies provided insight into the genes that were differentially expressed between MS patients and healthy controls, the issue of transcript-based disease heterogeneity was not addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, changes in gene expression in peripheral blood leukocytes might clarify the mechanism of MS relapses. Previous studies using microarray technology to measure gene expression changes in MS relapse had interesting results, but are limited by multiple factors, including the available microarrays, the use of unpaired samples, small sample sizes, and possible alteration of gene expression during sample preparation (5)(6)(7)(8). We have extended these findings using a larger population of subjects with paired relapse and stable samples from each, and comprehensive measurements of mRNA expression.…”
Section: Introductionmentioning
confidence: 84%
“…Dendrogram constructed using BRB ArrayTools with centered correlation and average linkage. The branch labels give the experiment number (1)(2)(3)(4)(5), the subject number (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), clinical status, treatment, and gender. The samples from the first two experiments formed large clusters.…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 99%